Treatment Strategies for Reducing Oil Contaminants in Wastewater - Juan Feron Ndruru; Ignatia Marlin Pongoh; Niken Adelia Agustin; Temmy Wikaningrum (Jurnal Serambi Engineering, 2022)
The more humans need to develop, the more waste will be generated from by-products of an industry's operational processes. One of the most waste in produce, namely wastewater contaminated by oil. Oil waste not only pollutes aquatic ecosystems but the impact of waste oil itself can be very dangerous for human health. Therefore, it is necessary to process wastewater contaminated with this oil. On the one hand, the development of innovation also makes the methods of processing contaminated waste more varied. Therefore, there is a need for a study to determine which wastewater treatment processes are effective, especially for wastewater that contains oil. This is the background for writing the journal "Treatment Strategies for Reducing Oil Contaminants in Wastewater". The research methodology of this journal itself uses a qualitative method with a literature review approach. So that the results obtained from the comparison of the efficiency of several processing methods such as membrane technology, electrocoagulation, adsorption, and combination. But even so, it still needs to be reworked related to the cost efficiency of each processing method.